2020
DOI: 10.9734/cjast/2020/v39i1530712
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Standard Precautions’ Practices among Health Care Workers in a Rural Area of South-South Nigeria

Abstract: Introduction: Occupational exposure to blood and body fluids (BBFs) is a serious public health concern and it constitute a major risk factor for transmission of infectious diseases such as hepatitis B virus (HBV), hepatitis C virus, and human immune deficiency virus. Therefore, regular adherence to standard precautions remains the best strategy advocated by World Health Organization and Centres of Disease Control for controlling occupational exposure to blood and body fluids. Objectives: To evaluate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Regarding different healthcare field specializations, Khubrani et al (2018) found no differences in SP knowledge among students in different healthcare disciplines, whereas other studies (both interventional and cross-sectional) that compared nurses, doctors, and students, and knowledge or practice found that doctors had slightly higher SP knowledge (Arinze-Onyia et al, 2018;Asmr et al, 2019;Goyal & Chaudhry, 2019). Nevertheless, some prior studies have reported better results for SP knowledge and compliance in nursing students and nurses than in other healthcare professionals (Ehimen et al, 2020;Haile et al, 2017;Kingston et al, 2018;Labrague et al, 2018;Tavolacci et al, 2008).…”
Section: Figurementioning
confidence: 91%
“…Regarding different healthcare field specializations, Khubrani et al (2018) found no differences in SP knowledge among students in different healthcare disciplines, whereas other studies (both interventional and cross-sectional) that compared nurses, doctors, and students, and knowledge or practice found that doctors had slightly higher SP knowledge (Arinze-Onyia et al, 2018;Asmr et al, 2019;Goyal & Chaudhry, 2019). Nevertheless, some prior studies have reported better results for SP knowledge and compliance in nursing students and nurses than in other healthcare professionals (Ehimen et al, 2020;Haile et al, 2017;Kingston et al, 2018;Labrague et al, 2018;Tavolacci et al, 2008).…”
Section: Figurementioning
confidence: 91%